Kinship Term in Indonesia: A Favorable Choice of Addressing Others - Ismiyani, Nining (Jurnal Visi Ilmu Pendidikan, 2014)
Addressing people has been an important issue for decades due to its sensitivity for mistaking the terms of address to various kinds of people. Misunderstanding brought by these terms of addressing people had happened since years ago (see many examples of the cases in Braun (1988). It is undeniably that such condition is still to be continued to recent times. That is why it is significant to simply know the habit of addressing people in one culture, as in this case Indonesia. Kinship term is a very familiar way of addressing others in Indonesia. This paper is describing how Kinship terms apply in Indonesia. It also delineates how Javanese culture, in which the population is the biggest in Indonesia influence the way Indonesians call each other.Keyword: addressing, kinship, culture